PENGEMBANGAN GAME EDUKASI JALUR REMPAH NUSANTARA BERBASIS CONSTRUCT PADA MATA PELAJARAN IPS KELAS VIII - Dinda Putri Ramadhan; Novrianti; Abna Hidayati; Alkadri Masnur (STKIP Subang, 2026)
The development of educational games as an effort to solve problems in Social Science subjects, the learning media used is still less varied, where there are several media used such as modules, LKPD and PowerPoint in learning which cause students to be less interested in learning Social Sciences and also less understanding of the material because there are no visual examples. Interactive media such as educational games are expected to be able to make students more interested in learning in Social Science subjects. This research uses the Research and Development (R&D) development method with a 4D development model consisting of Define, Design, Development, Disseminate stages. The validity test was carried out by 3 experts, namely 1 material validator and 2 media validators. The practicality test was carried out by grade VIII students. And the dissemination is carried out by spreading media links to MGMP IPS Padang City. Based on the validity test by material experts, the results were obtained with a percentage of 92.5% with the category